2023
DOI: 10.5455/ovj.2023.v13.i6.12
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spirulina supplementation on growth performance, puberty traits, blood metabolites, testosterone concentrations, and semen quality in Barki male lambs

Abstract: Background: The fertility and genetic value of the flock can be enhanced by selecting lambs with highly developed early puberty characteristics. Spirulina (SP) has been evaluated as a natural product supplement to boost lamb growth, immunity, and productivity. Aim: Study growth performance, blood metabolites, puberty development traits, semen quality, and seminal plasma biochemical concentrations of growing Barki lambs when supplemented with SP at different levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
2
2
0
Order By: Relevance
“…As for SP treatments for days 45 and 90, they didn't significantly affect the levels of lipids (CHOL, TG, HDL, LDL, and VLDL), except for a significant difference for the T3 factor in the levels of TG and VLDL. These results are consistent with the study of Mansour and Zeitoun [16], who didn't notice any significant effect of SP on TG levels. On the other hand, we disagree with it in terms of its effect on blood CHOL concentration.…”
Section: Very Low-density Lipoprotein (Vldl)supporting
confidence: 93%
See 1 more Smart Citation
“…As for SP treatments for days 45 and 90, they didn't significantly affect the levels of lipids (CHOL, TG, HDL, LDL, and VLDL), except for a significant difference for the T3 factor in the levels of TG and VLDL. These results are consistent with the study of Mansour and Zeitoun [16], who didn't notice any significant effect of SP on TG levels. On the other hand, we disagree with it in terms of its effect on blood CHOL concentration.…”
Section: Very Low-density Lipoprotein (Vldl)supporting
confidence: 93%
“…As for the interaction, it significantly affected the AST for both periods 45 and 90, while ALT was affected in period 90 and was not affected in period 45. These results agreed with the study of Mansour and Zeitoun [16] where they found a significant effect on the level of AST of SP treatments compared to the control treatment. On the other hand, there was a study by [22,25] who indicated that SP supplements led to a decrease in level of ALT and AST in blood serum of different breeds of sheep.…”
Section: Alanine Aminotransferase (Alt)supporting
confidence: 92%
“…It was placed on a hotplate inside a glass beaker and heated to 100°C for 20 minutes before being allowed to cool to room temperature. According to Mansour and Zeitoun (2023), the absorbance value of MDA was determined at 530nm.…”
Section: Measurement Of Serum Mda Levelsmentioning
confidence: 99%
“…For example, Wang et al (2023) examined increases in body score condition (BCS), body weight, and reproductive performance by supplementing Spirulina sp. Mansour and Zeitoun (2023) examined at growth performance, puberty, and blood metabolism in goats given Spirulina supplements; and Eldaim et al (2018) gave a combination of Spirulina sp. and Vitamin A supplements to goats in the late gestation phase, and the result was a decrease in fetal serum Tumor Necrosis Factor-alpha (TNFα).…”
Section: Introductionmentioning
confidence: 99%